ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA DITINJAU DARI GAYA BELAJAR KINESTETIK - Rosanggreni, Bunga Yana; Sugiarti, Titik; Yudianto, Erfan (Kadikma, 2018)
Abstract. This research purpose to analyze students error problem solving math story on the subject SPLDV in class X APH 2 SMKN 5 Jember, using Newman’s Error Analysis (NEA). The analyze will be related to the kinesthetic learning style. The research is descriptive qualitative. Data collection was done by tests, questionnaires and interviews. Based on the result of this research, kinesthetic students tend to make error on comprehension, transformation, process skill and encoding. Each students has their own unique way in solving the problem at every stage Newman. However, in general, students with kinesthetic learning style tend to solve problems with trial and error strategies and often misconceive because they do not understand what they mean when imagined. Keywords: Student, Newman’s Error Analysis, Mathematic Story, Kinesthetic Learning Style